2014
DOI: 10.1097/pec.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

A Computerized Child Passenger Safety Screening Program in the Emergency Department

Abstract: A child passenger safety program can be successfully implemented in the ED. A computerized nursing screening tool increases compliance with screening and providing needed car seats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…One safety class research study showed that interventions can increase knowledge regarding proper car seat use and improve attitudes regarding their importance but involve an hour-long class, which limits its practicality in resource poor environments as an intervention. 9 Computerized screening for car seat safety and distribution of car seats from the pediatric ED setting have been implemented. 11 A recent study demonstrated the possible utility of including information regarding CSDs in patient discharge instructions, although this is more challenging in the absence of an electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One safety class research study showed that interventions can increase knowledge regarding proper car seat use and improve attitudes regarding their importance but involve an hour-long class, which limits its practicality in resource poor environments as an intervention. 9 Computerized screening for car seat safety and distribution of car seats from the pediatric ED setting have been implemented. 11 A recent study demonstrated the possible utility of including information regarding CSDs in patient discharge instructions, although this is more challenging in the absence of an electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the capacity to improve patient knowledge and attitudes towards CSDs. One safety class research study showed that interventions can increase knowledge regarding proper car seat use and improve attitudes regarding their importance but involve an hour-long class, which limits its practicality in resource poor environments as an intervention 9 . Computerized screening for car seat safety and distribution of car seats from the pediatric ED setting have been implemented 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, this was recently reported in the USA where only about half of the children with motor vehicle crash fatalities wore any child restraints. 19 Child safety programmes initiated at the ED 20 have been reported and should be explored. Pedestrians, on the other hand, are known to be at high risk of severe injuries compared to other motorway users—this is especially applicable to older children who may not be supervised when crossing the roads.…”
Section: Discussionmentioning
confidence: 99%